Українська політична нація: витоки, історичні форми самоорганізації, сучасний стан - Лєбєдєва, Ю.О. (Сіверщина в історії України, 2022)
У статті досліджено витоки, історичні форми самоорганізації та сучасний стан української політичної нації. Акцентовано увагу на визначенні термінів «політична нація» та «українська політична нація», пов’язаних із наявністю в спільноті людей власної державності. Проаналізовано витоки української політичної нації. Указано, що Гетьманщина XVII–XVIII ст. була першим державним утворенням української модерної нації. Відзначено державні формування української політичної нації в період Української революції 1917–1923 рр. Проаналізовано стримування Російською імперією та СРСР процесу формування української політичної нації. Відзначено, що поява незалежної України стала фундаментом для формування суспільної групи українців. Зауважено, що вагоме значення для розвитку української політичної нації мають демократія та громадянське суспільство, цілісність держави, формування еліти, особливості менталітету українців, українська національна ідея, історична пам’ять, ідеологічний консенсус, мовне питання, міжнародні успіхи України, зростання рівня політичної культури її жителів, особливості економічного розвитку нашої країни. In article leaks, historical forms of selforganization and contemporary state of Ukrainian political nation were researched. Attention on definition terms «political nation» and «Ukrainian political nation» that connected whith statehood of people community availability was accented. Leaks of Ukrainian political nation were analysed. Pointed that Hetmanate of XVII–XVIII centuries was the first state formation of Ukrainian modern nation. State formations of Ukrainian political nation in the period of Ukrainian revolution 1917–1923 years were marked. Containment the process of becoming the Ukrainian political nation by Russian Empire and USSR was analysed. Marked that appearance of independent Ukraine became fundament for becoming community group of Ukrainians. Pointed that democracy and civil society have weighty value for Ukrainian political nation development. Obstacles on the way of democratization of Ukrainian society were marked. Value of state’s integrity in Ukrainian political nation development was separated. Contradiction of process of elite becoming in independent Ukraine was marked. Constructive and destructive issues of Ukrainians’ mentality for state-building were separated. Essence of Ukrainian national idea in independent Ukraine was analysed. Value of historical memory for modernization of Ukrainian political nation and appearance of Ukrainians’ ideological consensus was separated. Defensive function of language question was marked that is conditioned by overcoming consequences of Russification in USSR. Nessesarity of Ukraine’s strengthening on international arena was separated. Value of increasing level of Ukrainian political culture in becoming Ukrainian political nation was pointed. Economic dependence of Ukraine from Russian Federation as obstacle of Ukrainian community modernization was analysed.